Hypersensitive C-reactive protein-albumin ratio in endovascular treatment of acute ischaemic stroke clinical prognostic value - Cai, Youde; Zhongyong Peng; Xiong Zheng; Fang Gan; Qiansong He; Yunzhi Chen (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the specific quantitative relationship between the hypersensitive C-reactive protein-albumin ratio and short-term clinical outcome measures within 30 days of endovascular therapy in patients diagnosed with acute ischaemic stroke. Method: The retrospective study was conducted at the Jinyang Hospital, China, and comprised data from January 2019 to July 2023 of patients with acute large-vessel occlusive stroke who underwent endovascular therapy. The patients were stratified into two prognostic groups according to their 30-day postoperative modified Rankin Scale scores. Group A had patients with score 0-2 indicating good prognosis, and group B had patients with score 3-6 indicating poor prognosis. Baseline characteristics, vascular risk factors, laboratory test parameters, consultation duration, stroke subtype, responsible vessel and other relevant clinical data was noted and compared between the groups. Data was analysed using SPSS 25. Results: Of the 195 patients, 125(64%) were males and 70(36%) were females. The overall median age was 65 years (interquartile range: 54-74 years). There were 102(52.3%) patients in group A and 93(47.7%) were in group B. Advanced age, hypertension, cerebral oedema, haemorrhagic transformation, baseline National Institutes of Health Stroke score, white blood cell count, infarct volume and hypersensitive C-reactive protein-albumin ratio were significantly different between the groups (p<0.05). Receiver operating characteristic curve analysis revealed that C-reactive protein-albumin ratio predicted the highest value with area under the curve being 0.778. Conclusion: Elevated hypersensitive C-reactive protein-albumin ratio levels independently correlated with adverse clinical outcomes in acute ischaemic stroke patients undergoing endovascular therapy. Key Words: Hypersensitive C-reactive protein-albumin ratio, Endovascular treatment of acute, Acute ischaemic stroke, Prognostic.